2022
DOI: 10.3390/genes13020252
|View full text |Cite
|
Sign up to set email alerts
|

SPECC1L Mutations Are Not Common in Sporadic Cases of Opitz G/BBB Syndrome

Abstract: Opitz G/BBB syndrome (OS) is a rare genetic developmental condition characterized by congenital defects along the midline of the body. The main clinical signs are represented by hypertelorism, laryngo–tracheo–esophageal defects and hypospadias. The X-linked form of the disease is associated with mutations in the MID1 gene located in Xp22 whereas mutations in the SPECC1L gene in 22q11 have been linked to few cases of the autosomal dominant form of this disorder, as well as to other genetic syndromes. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…7 C ). Mutations in this region in SPECC1L have been identified in patients with the congenital developmental disorders Opitz G/BBB and Teebi hypertelorism ( 27 , 28 , 29 , 30 ) ( Fig. 7 B ), and previous studies suggested that disrupted MT association may contribute to the observed phenotypes.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…7 C ). Mutations in this region in SPECC1L have been identified in patients with the congenital developmental disorders Opitz G/BBB and Teebi hypertelorism ( 27 , 28 , 29 , 30 ) ( Fig. 7 B ), and previous studies suggested that disrupted MT association may contribute to the observed phenotypes.…”
Section: Resultsmentioning
confidence: 74%
“…Although not studied to the same extent, depletion of SPECC1L in cells led to defects in cytoskeletal organization, cell division, and migration ( 25 , 26 ), and SPECC1L mutations have been linked to developmental facial morphogenesis disorders that result in congenital malformations ( 25 , 27 , 28 , 29 , 30 ). The protein is found predominantly in the cytoplasm and has been shown to accumulate at both MT and filamentous actin structures throughout the cell cycle ( 25 , 31 ).…”
mentioning
confidence: 99%
“…S5c). Mutations in this region in SPECC1L have been identified in patients with the congenital developmental disorders Opitz G/BBB and Teebi hypertelorism [26]–[29] (Fig. 7a), and previous studies suggested that disrupted MT association may contribute to the observed phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Although not studied to the same extent, depletion of SPECC1L in cells led to defects in cytoskeletal organization and cell migration [25], and SPECC1L mutations have been linked to developmental facial morphogenesis disorders that result in congenital malformations [25]- [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation